Technologies,standards and applications of LTE-V2X for vehicular networks - Shanzhi CHEN; Jinling HU; Yan SHI; Li ZHAO (Dianxin kexue)
V2X (vehicle to everything) communication is the critical technology to provide environment sensing,information exchange and cooperative control capabilities in vehicular networks.LTE-V2X,as one of the major V2X communication standards initiated and mainly driven by Datang Telecom,can enable low latency,high reliability,high data rate and security in communications,as well as scale economies by sharing the existing LTE network and terminal chipsets.LTE-V2X communication technology was introduced,and compared with IEEE 802.11p standards.Then,the progress of LTE-V2X standardization,industrial research and development and trials and field testing works were provided.Finally,the development strategy of LTE-V2X and technical evolution towards 5G was discussed.